Evaluating the structural state of fluoride-oxide melts and their interactions with steel to sensible selection of ESR slag - Stepanenko , D.O.; Stovpchenko , G.P.; Togobitskaya , D.M.; Lisova , L.O. (Theory and Practice of Metallurgy, 2023)
Purpose. Evaluation of the structural state of slag melts in the CaF2-Al2O3-CaO system with varying contents of SiO2 (1; 2.5; 4 wt.%) and MgO (3; 6; 12 wt.%), based on their viscosity and electrical conductivity data, for a sensible selection of the optimal chemical composition that will ensure the efficiency of the electroslag process. Methodology. Correlation-regression analysis of the relationships between the properties of electroslag remelting slags and their chemical composition and temperature; adaptive segmented linear regression examination of the graphical dependence of the logarithms of viscosity (η) and electrical conductivity (χ) on temperature (ln(η,χ) = f(1/T)); thermodynamic modelling of the equilibrium composition of metal-slag-gas system phases using HSC Chemistry 9 software. Scientific novelty. A new approach is employed to assess the temperature ranges of structural changes induced by alterations in the energy barrier (activation energy) associated with the formation or dissociation of compounds and interactions between different types of ions. The approach is based on the analysis of temperature dependences of structure-sensitive properties (viscosity (η) and electrical conductivity (χ)) using the adaptive segment regression method. Practical value. The dependencies of the temperatures of the structural state changes (T1 – derived from viscosity data, T2 – derived from electric conductivity) and the intervals between them (∆Т) on the chemical composition of the studies slags can be reliably represented by the parameter ρ – stoichiometry index (the ratio of cations (Ca2+, Mg2+, Si4+, Al3+, etc.) to anions (O-, S2-, F- etc.)). The slag composition (wt.%) СаF2 – 31, Al2O3– 31, CaO– 31, SiO2–4, MgO–3 provides suitably low values of phase transition temperatures Т1 = 1454К, Т2 = 1153К and a wide range between them ∆T = 301 K that make it is promising for energy effective ESR in short-collar mold with ingot withdrawing.